Evaluation of typical hole-making strategies on mechanical behavior of CFRP/Ti single-lap bolted joints. (1st February 2023) - Zou, Fan; Dang, Jiaqiang; Chen, Tao; An, Qinglong; Chen, Ming
Graphical abstract: Highlights: Different hole-making processes were comprehensively investigated. The effects of hole-making processes on joint performance were revealed. The selection of optimal scheme considering multiple-criteria was proposed. Abstract: Carbon fiber–reinforced polymer (CFRP) and Ti6Al4V alloy are often jointed with numerous bolts in the load-bearing structure of aircraft. The hole-making process plays an essential role in determining joint performance. Selection of a suitable hole-making process is vital for the application of CFRP/Ti bolted joints. This paper aims to evaluate the typical mechanical hole-making processes of CFRP/Ti stacks and reveal their influence mechanism on the mechanical behavior of single-lap bolted joints. Typical hole-making processes are systematically investigated and compared by applying machining and mechanical tests. The obtained results show that the hole diameter of CFRP layer is determined by the severity of the hot and continuous Ti-chips induced by the micro-cutting effect. The stiffness and strength of joints with different hole size characteristics are different, which can be attributed to the existence of micro-stress concentration. Each hole-making process has its advantages and disadvantages. This work provides a multi-criteria evaluation scheme as a basis for hole-making process selection in the aerospace industry.